Refuting the challenges of the developmental shift of polarity of GABA actions: GABA more exciting than ever! - Ben-Ari, Yehezkel; Woodin, Melanie A.; Sernagor, Evelyne; Cancedda, Laura; Vinay, Laurent; Rivera, Claudio; Legendre, Pascal; Luhmann, Heiko J.; Bordey, Angelique; Wenner, Peter; Fukuda, Atsuo; van den Pol, Anthony N.; et al. (Frontiers in Cellular Neuroscience, 2012)
Abstract During brain development, there is a progressive reduction of intracellular chloride associated with a shift in GABA polarity: GABA depolarizes and occasionally excites immature neurons, subsequently hyperpolarizing them at later stages of development. This sequence, which has been observed in a wide range of animal species, brain structures and preparations, is thought to play an important role in activity-dependent formation and modulation of functional circuits. This sequence has also been considerably reinforced recently with new data pointing to an evolutionary preserved rule. In a recent ‘Hypothesis and Theory Article’, the excitatory action of GABA in early brain development is suggested to be “an experimental artefact” (Bregestovski and Bernard, 2012). The authors suggest that the excitatory action of GABA is due to an inadequate/insufficient energy supply in glucose-perfused slices and/or to the damage produced by the slicing procedure. However, these observations have been repeatedly contradicted by many groups and are inconsistent with a large body of evidence including the fact that the developmental shift is neither restricted to slices nor to rodents. We summarize the overwhelming evidence in support of both excitatory GABA during development, and the implications this has in developmental neurobiology.